Breast Cancer Risk Analysis Using Fuzzy Inference System with the Mamdani Model: Literature Review - Siti utami dewi; Rr. Tutik Sri Haryati (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2021)
Breast cancer is one of the most common cancer causes of death in sufferers. Breast cancer is the second leading cause of death for Indonesian women. For this reason, a device that can identify the risk of breast cancer is needed. The fuzzy method with the Mamdani model is one method that has been widely used in software development to determine the level of breast cancer risk. Purpose: To know the software development of the Fuzzy Inference System Method with the Mamdani model to identify the level of breast cancer risk. Methods: This research is a literature study with the data collection process through the PubMed, Science Direct, ProQuest, and Google Scholar databases. The criteria for the articles used are 2010-2021 publications. Results: Based on a review of 10 journals using the Fuzzy Inference System (FIS) Mamdani model can provide effective results to identify risks for people who have the possibility of developing breast cancer. Conclusion: The fuzzy expert system using the Mamdani method can be applied to the problem domain of breast cancer diagnosis with a fairly good level of accuracy to be able to overcome the inequality of mammography results.